Influence of Heat Stress in Poultry Production and Approaches to Combat It - Shekhar, Shashank; Dalai, Nirupama; Mohapatra, Swagat (International Journal of Livestock Research, 2018)
Temperature and moisture of air are two major environmental factors controlling the heat stress of livestock. The general signs of heat stress in poultry includes open mouth panting while spreading their wings and squatting close to the ground, gasping, lethargic and droopy acting, closed eyes, lying down, decreased appetite, increased thirst, drop in egg production, reduced body weight, increased cannibalism etc. Heat stress during the growth period of broilers has been associated with undesirable meat characteristics and quality loss. The blood biochemical parameters have also been found deviated than the normal values. The immunity of the birds also affected during heat stress. Ventilation, bird density and nutrition are a few areas that play a role in controlling heat accumulation. Nutritional manipulations, such as addition of fat and reduction of excess protein along with vitamin, minerals and electrolyte supplementations have been reported to reduce mortality due to heat stress.